Wnt signaling controls pro-regenerative Collagen XII in functional spinal cord regeneration in zebrafish - Wehner, Daniel; Tsarouchas, Themistoklis M.; Michael, Andria; Haase, Christa; Weidinger, Gilbert; Reimer, Michell M.; Becker, Thomas; Becker, Catherina G. (Nature Communications, 2017)
The inhibitory extracellular matrix in a spinal lesion site is a major impediment to axonal regeneration in mammals. In contrast, the extracellular matrix in zebrafish allows substantial axon re-growth, leading to recovery of movement. However, little is known about regulation and composition of the growth-promoting extracellular matrix. Here we demonstrate that activity of the Wnt/β-catenin pathway in fibroblast-like cells in the lesion site is pivotal for axon re-growth and functional recovery. Wnt/β-catenin signaling induces expression of col12a1a/b and deposition of Collagen XII, which is necessary for axons to actively navigate the non-neural lesion site environment. Overexpression of col12a1a rescues the effects of Wnt/β-catenin pathway inhibition and is sufficient to accelerate regeneration. We demonstrate that in a vertebrate of high regenerative capacity, Wnt/β-catenin signaling controls the composition of the lesion site extracellular matrix and we identify Collagen XII as a promoter of axonal regeneration. These findings imply that the Wnt/β-catenin pathway and Collagen XII may be targets for extracellular matrix manipulations in non-regenerating species.
CRIS-Team Scopus Importer:2022-08-03